PENGARUH KUALITAS LAYANAN M-BANKING TERHADAP KEPUASAN NASABAH (STUDI KASUS: MAHASISWA FAKULTAS EKONOMI & BISNIS UNIVERSITAS HKBP NOMMENSEN MEDAN) - Simanjuntak, Sri Damai; Nainggolan, Erni Yuli Sari; Silalahi, Elly Dayanti; Panjaitan, Rizky Alexander; Pardosi, Ririn Wantika; Hasugian, Christnova; Siallagan, Hamonangan (Komunitas Manajemen Kompetitif, 2025)
This research aims to examine the influence of mobile banking service quality on customer satisfaction. The population of this study consists of 1.778 students from the Faculty of Economics and Business, HKBP Nommensen University. The sampling technique used is Non-Probability Sampling employing simple random sampling, resulting in a sample of 95 students. Primary data was collected through a questionnaire. A quantitative method using simple linear regression analysis was employed in this research. The research findings indicate that service quality has a positive and significant effect on customer satisfaction, as evidenced by the t-value > t-table (15.190 > 1.66140) and a significance value of 0.000 < 0.10. The Coefficient of Determination (R2) is 0.683, signifying that 68.3% of Customer Satisfaction as the dependent variable (Y) is determined by Service Quality (X), while the remaining 31.7% is determined by other variables beyond those studied. Keywords: Service quality, Customer Satisfaction, Mobile banking